Progressive electrocardiographic changes in parallel with cardiac magnetic resonance findings in fabry disease. (25th November 2020) - Figliozzi, S; Camporeale, A; Pieroni, M; Pieruzzi, F; Namdar, M; Lusardi, P; Spada, M; Mignani, R; Burlina, A; Scolari, F; Carrubbi, F; Battaglia, Y; et al.
Abstract: Background: Cardiac Magnetic Resonance (CMR) allows to detect progressive stages of cardiac involvement in Fabry Disease (FD). A systematic description of electrocardiographic (ECG) alterations occurring in FD is currently missing. Purpose: To explore ECG changes in progressive stages of FD cardiomyopathy. Methods: 71 FD patients and 17 healthy controls underwent CMR with T1 mapping and 12-lead ECG. ECG analysis included the duration of the P-wave and the interval between the end of P-wave and the beginning of QRS (PendQ). FD patients in the test cohort were divided into 3 groups with increasing severity of cardiac involvement: A) normal T1, no LVH; B) low T1, no LVH; C) low T1, LVH. Results: An increase of Pwave/PendQ ratio was observed in Group A compared to Controls (1.08 vs. 0.75, p<0.0001). Higher Pwave/PendQ ratio (1.50 vs. 1.08, p<0.0001), shorter PQc interval (127.9 vs. 159.5, p=0.0007), increased Sokolow-Lyon Index (SLI) (3.2 vs. 2.4, p<0, 001) and T wave amplitude (0.6 vs. 0.4 mV, p=0.002) characterized Group B in comparison with Group A. A higher prevalence of left bundle branch blocks (13.6% vs. 0%, p=0.03) and repolarization abnormalities (77.3% vs. 5.7%), wider QRS (120 vs 95 msec, p<0.0001) and QT (460 vs 400 msec, p=0.003) intervals were found in Group C compared to Group B. SLI (AUC 0.769), Pwave/PendQ (AUC 0.778), QRS (AUC 0.703) and QT (AUC 0.769) durations resulted to be independent predictors of low T1 values on CMR at stepwise multivariate analysis. Conclusion: FD is characterized by progressive ECG changes. The identification of ECG parameters able to predict a lowering of myocardial T1 values on CMR may promote early detection of cardiac involvement, helping to target the therapeutic approach. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): This study was partially supported by Ricerca Corrente funding from the Italian Ministry of Health to IRCCS Policlinico San Donato.